A comparative study on hemodynamic changes in patients undergoing simple tooth extractions utilizing local anesthetics with vasoconstrictors epinephrine and norepinephrine - Climaco, Christine R.
Forty-eight Filipino subjects, 23 males and 25 females, between ages 20-40 years (mean age = 28.3 years), without any systemic conditions were selected. Simple tooth extractions of not more than 3 teeth were done, utilizing not more than 2 cartridges of local anesthetic. Twenty-three patients were given 2% Lidocaine with 1:80,000 Epinephrine (Xylocaine), while 25 patients were given .4% Propoxycaine and 2% Procaine with 1:30,000 Norepinephrine (Ravocain HC1). All procedures took no more than 45 minutes, beginning with the application of the local anesthetic. Measurement of heart rate and blood pressure were taken at 5 points during the procedure: (1) 30-80 minutes prior to entering the operatory, (2) when the patient was seated on the dental chair, (3) during injection of the local anesthetic, (4) during extraction, and (5) 5 minutes after extraction. Results showed that there was no significant difference between changes in the heart rate and blood pressure.